Granting a compulsory will to grandfather and grandmother based on Aristotle's distributive theory - Kasuwi Saiban; Titi Rusydiyati Al Kaswy; Fadil SJ (Faculty of Law, University of Merdeka Malang, 2022)
There is no legal basis for giving testament wajibah to a grandparent in Indonesia. However, the Religious Courts of Tarakan, in decision number: 610/Pdt.G/2014/PA.Trk. the judges gave testament wajibah portion of the inheritance to the grandparent because the heir’s mother blocked their position and the parenting role carried out by the grandparent since the mother left the heir, and her existence was unknown. The judge’s decision must consider the principles of legal certainty, benefits, and a sense of justice for the parties. Therefore, this research focuses on the judge’s legal reasoning in decision number: 610/Pdt.G/2014/PA.Trk. and how the judge’s decision is seen from the perspective of Aristotle’s distributive justice theory. This research is juridical-normative with cases and conceptual approaches. The results showed that the judge’s legal reasoning through the process of de heuristic and de legitimate, legal basis that judges used are the holy Qur’an, hadith, KHI, and Islamic law. The judges consider the role of grandparents during the heir to life. And giving testament wajibah to grandparents is considered fair based on Aristotle’s distributive justice theory because they have fulfilled the proportional principle requirements.How to cite item: Saiban, K., Al Kaswy, T., SJ, F. (2022). Granting a compulsory will to grandfather and grandmother based on Aristotle's distributive theory. Jurnal Cakrawala Hukum, 13(3), 272-280. DOI:https://doi.org/10.26905/idjch.v13i3.8855.